(untitled) (Interdisciplinary Studies Journal, 2026)
This work addresses biomonitoring of trace atmospheric pollutants using Tillandsias, mosses, and lichens. A scientometric analysis was conducted using Scopus and Web of Science, with 249 records selected. Passive biomonitoring was dominant ( 52%), while active monitoring represented 36%. Moss was most used ( 52%), likely due to its natural abundance in Asia, followed by lichens (28%) and Tillandsias (11%). Main characterization techniques included ICP-MS/OES, INAA, XRF, and AAS. Urban (35%) and industrial (38.4%) environments were the most studied. Despite some limitations, biomonitoring is a powerful, low-cost tool and a nature-based solution, especially suitable for low-income regions. Russia and Romania stand out in adoption in the period of this research (2020 – 2025), but the Americas and Africa show a lack of incentives, highlighting the need for greater global support. Factors that can interfere with analysis were also discussed (differences among species, requirements for active monitoring, interference of meteorological conditions, and particulate matter capture by plants).